Project Oosteroeverduinen Oostende - Bossu, Peter; Vandenbroucke, Guido; Belmans, Guido ([Oostende]: Buitengoed cvba, 2011)
"Tekst en samenstelling: Peter Bossu, Guido Vandenbroucke, Ghislain Belmans"